Pengaruh Customer Satisfaction, Brand Trust, dan Customer Feedback Terhadap Customer Loyalty Pada Perusahaan Mobil Suzuki - Arianto, Jhony Putra Satria (AL-QARDH, 2016)
The background of this research to understand the importance of customer satisfaction will result customer loyalty on consumer